Perlindungan Hukum Terhadap Pekerja PT. Mara Jaya Dalam Hal Kebebasan Berserikat Menurut Undang-Undang RI Nomor 21 tahun 2000 Tentang serikat pekerja - Jauhari Ginting (Universitas Islam Sumatera Utara, 2019)
Freedom of association and assembly and also expression of opinion are basic rights possessed by citizens of a democratic sovereignty of the people. Based on this, the problem in this thesis is how to regulate the legal protection of workers in terms of freedom of association, how the implementation of legal protection for workers in terms of freedom of association at PT. Mara Jaya, what are the obstacles in terms of freedom of association implementation and how to overcome these obstacles to PT. Mara Jaya. This writing uses the library research method to study secondary data related to the problems and field research by conducting interviews and collecting data to the Chairman of PT. Mara Jaya Medan.The legal protection arrangement for workers in terms of freedom of association is a guarantee to create a harmonious relationship between workers and employers as partners. Through a healthy industrial relationship, there will be guarantee of an equal position between the worker and the employer, the production process runs smoothly and business activities will not be interrupted and the worker will obtain welfare and guarantee of life until his old age. Implementation of legal protection for workers in terms of freedom of association at PT. Mara Jaya was not initially implemented. However, nowadays, it has been carried out in accordance with the provisions of the legislation that is protecting the rights of members, participating in maintaining order for the continuation of production, distributing aspirations in a democratic manner, developing the skills and